The art athlete: a sports biomechanics perspective - Elliott, B.; Alderson, J.; Ackland, T.; Hopper, L. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
Overuse injuries are as much a problem for `art athletes` (dancers and musicians and performing artists generally) as they are for those we more commonly term `athletes`. Lower back injuries in male ballet dancers are certainly commonplace. 3D motion analysis in combination with 3D Static Strength Predicting analysis showed that compressive forces at L5/S1 were above the National Institute of Occupational Safety and Health `Back Compression Design Limit` (~ 4,500N) and shear forces were high (~ 530 N) for male dancers performing two commonly used classical lifts. A research design for the use of an opto-reflective motion analysis (Vicon) to investigate shoulder joint loading in cellists and violinists will also be presented.